Conflict and diplomacy US and the birth of Bangladesh, Pakistan divides - Singh, Jaswant 1938-2020; Bhåaòtiyåa, Såuraja (Rupa & Company, 2008)
On US diplomatic relations with South Asian countries during the emergence of Bangladesh.